The fusion of hard and soft Pomerons: 3-jet diffractive production - V. A. Khoze; A. D. Martin; M. G. Ryskin; A. G. Shuvaev; I. V. Surnin (European Physical Journal C: Particles and Fields, 2019)
Abstract We consider the central exclusive production of high $$E_T$$ ET jets $$pp→ p+(X+dijet)+p$$ pp→p+(X+dijet)+p . In particular we study the possible contamination of the purely exclusive signal by semi-exclusive production where no other secondaries are emitted in one hemisphere, between the highest $$E_T$$ ET dijet and the recoil proton, while in the other hemisphere a third jet, plus possibly additional hadron activity, is allowed, but still separated from the incoming proton by a large rapidity gap. This process arising from the fusion of a hard and a soft Pomeron has not been considered before. It turns out that it gives a negligible contribution. The calculation involves a careful treatment of the QCD colour structure of the amplitudes.